Deficiency of miR‐208a Exacerbates CCl4‐Induced Acute Liver Injury in Mice by Activating Cell Death Pathways. Issue 10 (19th August 2020) - Bala, Shashi; Calenda, Charles D.; Catalano, Donna; Babuta, Mrigya; Kodys, Karen; Nasser, Imad A.; Vidal, Barbara; Szabo, Gyongyi
Abstract : Acute liver injury (ALI) is associated with multiple cellular events such as necrosis, apoptosis, oxidative stress and inflammation, which can lead to liver failure. In this study, we demonstrate a new role of microRNA (miR)‐208a in ALI. ALI was induced in wild‐type (WT) and miR‐208a knockout (KO) mice by CCl4 administration. Increased alanine aminotransferase and decreased hepatic miR‐208a levels were found in WT mice after acute CCl4 treatment. Histopathological evaluations revealed increased necrosis and decreased inflammation in miR‐208a KO compared with WT mice after CCl4 treatment. CCl4 treatment induced a higher alanine aminotransferase elevation and increased numbers of circulating extracellular vesicles (exosomes and microvesicles) in miR‐208a KO compared with WT mice. We found increased CCl4 ‐induced nuclear factor kappa B activation and tumor necrosis factor‐α induction and decreased monocyte chemoattractant protein 1 levels in miR‐208a KO compared with WT mice. Terminal deoxynucleotidyl transferase–mediated deoxyuridine triphosphate nick‐end labeling assay indicated aggravated hepatic apoptosis and necrosis in CCl4 ‐ treated miR‐208a KO compared with WT mice. CCl4 treatment induced a greater increase in cleaved caspase‐8, p18, and caspase‐3 in miR‐208a KO compared with WT mice. p53 is involved in various cell death pathways, including necrosis and apoptosis. Our in silico analysis revealed p53 as a predicted miR‐208a target, and we found enhanced p53 and cyclophilin D protein expressions in miR‐208a KO mice after CCl4 treatment. Increased liver injury in miR‐208a KO mice was further associated with increased Bax (B cell lymphoma 2–associated X protein) and p21 expression. Our in vitro results indicated a role of miR‐208a in cell death. We found that CCl4 ‐induced cytotoxicity was partially rescued by miR‐208a overexpression in RAW macrophages. Altogether, our results revealed a role of miR‐208a in ALI in mice and suggest a role for miR‐208a in regulating cell death. Abstract : In this manuscript, we demonstrate a new role of miR‐208a in acute liver injury. Our results revealed a novel role of miR‐208a in acute liver injury in mice and suggest a role for miR‐208a in the regulation of hepatocyte apoptosis and necrosis.